Applicability of droplet digital polymerase chain reaction for minimal residual disease monitoring in Philadelphia‐positive acute lymphoblastic leukaemia. Issue 5 (16th August 2021) - Ansuinelli, Michela; Della Starza, Irene; Lauretti, Alessia; Elia, Loredana; Siravo, Veronica; Messina, Monica; De Novi, Lucia Anna; Taherinasab, Akram; Canichella, Martina; Guarini, Anna; Foà, Robin; Chiaretti, Sabina
Abstract: In Ph+ acute lymphoblastic leukaemia (Ph+ ALL), minimal residual disease (MRD) is the most relevant prognostic factor. Currently, its evaluation is based on quantitative real‐time polymerase chain reaction (Q‐RT‐PCR). Digital droplet PCR (ddPCR) was successfully applied to several haematological malignancies. We analyzed 98 samples from 40 Ph+ ALL cases, the majority enrolled in the GIMEMA LAL2116 trial: 10 diagnostic samples and 88 follow‐up samples, mostly focusing on positive non‐quantifiable (PNQ) or negative samples by Q‐RT‐PCR to investigate the value of ddPCR for MRD monitoring. DdPCR BCR/ABL1 assay showed good sensitivity and accuracy to detect low levels of transcripts, with a high rate of reproducibility. The analysis of PNQ or negative cases by Q‐RT‐PCR revealed that ddPCR increased the proportion of quantifiable samples ( p  < 0.0001). Indeed, 29/54 PNQ samples (53.7%) proved positive and quantifiable by ddPCR, whereas 13 (24.1%) were confirmed as PNQ by ddPCR and 12 (22.2%) proved negative. Among 24 Q‐RT‐PCR‐negative samples, 13 (54.1%) were confirmed negative, four (16.7%) resulted PNQ and seven (29.2%) proved positive and quantifiable by ddPCR. Four of 5 patients, evaluated at different time points, who were negative by Q‐RT‐PCR and positive by ddPCR experienced a relapse. DdPCR appears useful for MRD monitoring in adult Ph+ ALL.